Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. Emotional intelligence’ among secondary school teachers in Bahri localityGhada Al- Ameen Ahmed 2. The reality of the practice of the teachers of the lower basic stage of blended education and its reflection on the application of differentiated education from their point of view in the schools of the Directorate of Education in South HebronFerial Abdulaziz Mohammad Amro 3. Developing the performance of female educational supervisors in Jazan region in the view of contemporary trends of educational supervisionAishah Mahah Safhi 4. Home schooling: It’s justifications and importance of its application applying it in Saudi Arabia in light of Islamic Educational PrinciplesAli Abdullah Ahmed Al-Zahrani 5. Psychological well-being and its relationship to religious behavior among students of Sultan Qaboos University - Sultanate of OmanHilal Salim Sulaiman Alabri 6. Cognitive Bias and its Relationship to Learning Motivation among Umm Al-Qura University StudentsDayana Fahmi Ali Hammad - Shuruq Abdullah Muhammad Baothman7. The level of Insurance awareness among private school teachers in the capital's Secretariat Sana'aMrs. Yasmine Yehia Abdel-Qader Al-Khatari, Co-Prof. Eman Saleh Al-Sanabani
Keywords: Journal of Educational and Psychological Sciences